Taxonomic revision of Perdita subgenus Heteroperdita Timberlake (Hymenoptera: Andrenidae), with descriptions of two ant-like males - Portman, Zachary M.; Neff, John L.; Griswold, Terry (Zootaxa, 2016)
Perdita subgenus Heteroperdita Timberlake, a distinctive subgenus of 22 species from the southwestern United States and adjacent Mexico, all specialists on Tiquilia (Boraginaceae), is revised. Nine new species are described: Perdita (Heteroperdita) desdemona Portman, sp. n., P. (H.) exusta Portman & Griswold, sp. n., P. (H.) hippolyta Portman & Griswold, sp. n. (male previously incorrectly described as P. pilonotata Timberlake), P. (H.) hooki Portman & Neff, sp. n., P. (H.) nuttalliae Portman, sp. n., P. (H.) prodigiosa Portman & Griswold, sp. n., P. (H.) sycorax Portman, sp. n., P. (H.) titania Portman & Griswold, sp. n., and P. (H.) yanegai Portman, sp. n. The following sexes are associated and described for the first time: the male of P. (H.) frontalis Timberlake, 1968, the female of P. (H.) optiva Timberlake, 1954, and the true male of P. (H.) pilonotata Timberlake, 1980. Perdita (H.) fasciatella Timberlake, 1980 is proposed as a junior synonym of P. (H.) sexfasciata Timberlake, 1954. A neotype is designated for P. (H.) pilonotata Timberlake, 1980. Two species in particular, P. prodigiosa and P. pilonotata, are sexually dimorphic with distinctive ant-like males. Information is presented on floral relationships, phenology, and geographic distribution. Identification keys for males and females are provided.